Efektivitas Pemberian Kunyit Asam terhadap Penurunan Skala Nyeri Dismenore Pada Remaja Putri di SMAN 2 Karawang - Fadhillah, Anisa Candra Rini; Futriani, Elfira Sri (Universitas Malahayati, 2025)
ABSTRACT According to data from the World Health Organization (WHO) in 2016, the prevalence of menstrual pain is quite high in various countries with the average incidence of menstrual pain in adolescent girls between 17% and 81%. In Indonesia, the prevalence of primary menstrual pain, where three quarters experience mild to severe pain and the remainder experience severe menstrual pain. The impact of primary dysmenorrhea causes young women to experience decreased concentration, feel weak when studying and choose to remain silent in class. To determine the effectiveness of giving tamarind turmeric to reduce the pain scale of dysmenorrhea in adolescent girls. Quasy experiment using a pretest posttest with control group design. The sampling technique used a total sampling of 30 respondents. The analysis used is univariate and bivariate test analysis using the paired simple t test with the SPSS version 26 program. The frequency distribution of the intensity of menstrual pain before being given turmeric acid was mostly moderate pain (60.0%) and after being given turmeric acid was mild pain (60.0%). The frequency distribution of menstrual pain intensity in the pre-test control group was mostly moderate pain (80.0%) and post-test mild pain (66.7%).There is effectiveness of giving tamarind turmeric in reducing the dysmenorrhea pain scale in young women and there is a difference in the effect of giving tamarind turmeric between the experimental group and the control group. It is hoped that young women who experience menstrual pain are encouraged to consume tamarind turmeric to reduce menstrual pain and reduce the use of pharmacological drugs to treat the pain. Keywords: Tamarind Turmeric, Dysmenorrhea, Pain ABSTRAK Menurut data World Health Organization (WHO) pada 2016, prevalensi kejadian nyeri menstruasi cukup tinggi di berbagai negara dengan rata-rata insiden terjadinya nyeri menstruasi pada remaja putri antara 17% hingga 81%. Di Indonesia, prevalensi nyeri menstruasi primer, di mana tiga perempat mengalami nyeri ringan hingga berat dan sisanya mengalami nyeri menstruasi tingkat berat. Dampak dismenore primer menjadikan remaja putri mengalami penurunan konsentrasi, meras lemas saat pembelajaran dan memilih berdiam diri di kelas. Mengetahui efektivitas pemberian kunyit asam terhadap penurunan skala nyeri dismenore pada remaja putri. Quasy eksperimen menggunakan rancanganpretest posttest with control group design. Teknik pengambilan sampel menggunakan total Sampling sebanyak 30 responden. Analisa yang dipakai yaitu analisa uji univariat dan bivariat dengan uji paired simple t test dengan program SPSS versi 26. Distribusi frekuensi intensitas nyeri haid sebelum diberikan kunyit asam sebagian besar dengan nyeri sedang (60,0%) dan sesudah diberikan kunyit asam dengan nyeri ringan (60,0%). Distribusi frekuensi intensitas nyeri haid pada kelompok kontrol pre test sebagian besar dengan nyeri sedang (80,0%) dan post test dengan nyeri ringan (66,7%). Ada efektivitas pemberian kunyit asam terhadap penurunan skala nyeri dismenore pada remaja putri dan terdapat perbedaan pengaruh pemberian kunyit asam antara kelompok eksperimen dan kelompok kontrol.Diharapkan kepada Remaja putri yang mengalami nyeri menstruasi dianjurkan menkonsumsi kunyit asam untuk mengurangi nyeri menstruasi dan mengurangi penggunaan obat-obatan farmakologi untuk mengatasi nyerinya. Kata Kunci: Kunyit Asam, Dismenore, Nyeri